2022
DOI: 10.1038/s41380-022-01907-x
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting early life stress-induced adolescent depression through epigenomic approach

Abstract: Early life stress (ELS), such as abuse and neglect during childhood, can lead to psychiatric disorders in later life. Previous studies have suggested that ELS can cause profound changes in gene expression through epigenetic mechanisms, which can lead to psychiatric disorders in adulthood; however, studies on epigenetic modifications associated with ELS and psychiatric disorders in adolescents are limited. Moreover, how these epigenetic modifications can lead to psychiatric disorders in adolescents is not fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 207 publications
1
8
0
Order By: Relevance
“…It has been demonstrated that miRNAs form highly correlated networks in the brains of patients with MDD that differ from healthy controls, indicating that miRNA networks can cause specific behavioral phenotypes. In rats it has been demonstrated that rats which show learned helplessness, a clinical phenotype indicative of suicide risk, have a diminished miRNA response in the frontal cortex to acute stress compared to controls, indicating that anomalous expression of miRNAs results in defects in the stress coping response [ 52 ].…”
Section: Environmental Factors Acting Epigenetically In Psychiatric D...mentioning
confidence: 99%
“…It has been demonstrated that miRNAs form highly correlated networks in the brains of patients with MDD that differ from healthy controls, indicating that miRNA networks can cause specific behavioral phenotypes. In rats it has been demonstrated that rats which show learned helplessness, a clinical phenotype indicative of suicide risk, have a diminished miRNA response in the frontal cortex to acute stress compared to controls, indicating that anomalous expression of miRNAs results in defects in the stress coping response [ 52 ].…”
Section: Environmental Factors Acting Epigenetically In Psychiatric D...mentioning
confidence: 99%
“…Specifically, they serve as biomarkers for diagnosing depression and anxiety and tracking therapeutic responses to these conditions [ 10 ]. A lot of recent research has proved the relationship between ncRNAs and depression [ 11 , 12 ]. For instance, siRNA can be an effective experimental tool to study depression [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide associations studies (GWAS) have identified over 200 MDD risk loci 1113 ; however, similarly to other psychiatric phenotypes, characterizing the functional impact of such variants has remained challenging as they mostly map outside protein-coding regions. In addition to genetic variation, the adverse effects of environmental factors, such as early-life stress, on increasing the risk for depression 14,15 , are mediated by regulatory changes 16 . Single-cell atlases of open chromatin cis-regulatory elements (cCREs) holds promise to uncover mechanisms whereby disease-associated risk-variants may impact cell-specific gene-regulatory targets 17,18 .…”
Section: Introductionmentioning
confidence: 99%